ANALISIS PERILAKU BRAND SWITCHING DALAM PEMBELIAN PRODUK HANDPHONE - Rahmat Agus Santoso (Universitas muhammadiyah malang, 2011)
Fakultas Ekonomi Universitas Muhammadiyah GresikE-mail: ra_santosa@yahoo.co.id.ABSTRACTThis study aimed to identify factors that influence consumers’ brand switching behavior in the purchaseof mobile products in the district Undergraduate Theses. This study uses samples of 100 respondents,the type of data used in the primary. Data collection techniques using questionnaires andmultiple linear regression analysis tool. The results demonstrated that the factor of price, satisfactionand quality simultaneously and partially have influence over purchasing decisions. All three of thesefactors, the most dominant influence on purchase decisions is the price factor.Keywords: price, customer satisfaction and quality.